PENGARUH QUALITY THE WORK LIFE (QWL), DAN PEMBERDAYAAN TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOUR (OCB) DENGAN MEDIASI KEPUASAN KERJA - Sapto Widiaspono; Bambang Suko Priyono (Fakultas Ekonomi Universitas Pekalongan, 2022)
This study to determine whether Quality The Work Life and empowerment have an effect in Organizational Citizenship and Job Satisfaction as mediating variables for supporting staff for Perda and Perkada enforcement activities in the Satpol PP Agency of Pekalongan City. The method used is a quantitative method with 120 members of the Satpol PP research subject. Linear regression in Software version 19 was used as a data analysis method. From this research, it shows that there is a positive and significant effect of Quality of Work Life (QWL) on Job Satisfaction in the Satpol PP Agencies of Pekalongan City. There is a positive and significant effect of Quality of Work Life (QWL) on Organizational Citizenship Behavior (OCB) in the Satpol PP Agency of Pekalongan City, there is a positive and insignificant effect of Empowerment on Organizational Citizenship Behavior (OCB), Job Satisfaction has a positive and significant effect on Organizational Citizenship Behavior (OCB). From the results of the Sobel test, Job Satisfaction mediates the effect of Quality The Work Life (QWL) on Organizational Citizenship Behavior (OCB). And for the Empowerment of Organizational Citizenship Behavior (OCB) mediated by job satisfaction, because empowerment is not significant to Organizational Citizenship Behavior (OCB), job satisfaction mediates the total effect of Empowerment on OCB with Job Satisfaction results being able to mediate the relationship between the two effects